2013
DOI: 10.1007/s12576-013-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

Lobe-related concentration- and Ca2+-dependent interactions of calmodulin with C- and N-terminal tails of the CaV1.2 channel

Abstract: This study examined the bindings of calmodulin (CaM) and its mutants with the C- and N-terminal tails of the voltage-gated Ca(2+) channel CaV1.2 at different CaM and Ca(2+) concentrations ([Ca(2+)]) by using the pull-down assay method to obtain basic information on the binding mode, including its concentration- and Ca(2+)-dependencies. Our data show that more than one CaM molecule could bind to the CaV1.2 C-terminal tail at high [Ca(2+)]. Additionally, the C-lobe of CaM is highly critical in sensing the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Some other experiments have demonstrated that CDI in the L‐type channel (Cav1.2) is governed by the binding of Ca 2+ to C‐lobe of CaM [3,8,9]. Our previous studies have also shown that C‐lobe of CaM is critical in sensing the change of [Ca 2+ ] when it binds to the C‐terminal tail of Cav1.2 [10]. However, when we observed the facilitation and inactivation of Cav1.2 activity induced by Ca 2+ ‐insensitive mutants of CaM with patch‐clamp technique, we found that the Ca 2+ ‐dependency requires both N‐ and C‐lobe [11,12].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Some other experiments have demonstrated that CDI in the L‐type channel (Cav1.2) is governed by the binding of Ca 2+ to C‐lobe of CaM [3,8,9]. Our previous studies have also shown that C‐lobe of CaM is critical in sensing the change of [Ca 2+ ] when it binds to the C‐terminal tail of Cav1.2 [10]. However, when we observed the facilitation and inactivation of Cav1.2 activity induced by Ca 2+ ‐insensitive mutants of CaM with patch‐clamp technique, we found that the Ca 2+ ‐dependency requires both N‐ and C‐lobe [11,12].…”
Section: Introductionmentioning
confidence: 86%
“…The Ca 2+ ‐insensitive mutants of N‐lobe (N‐lobe 12 , E31A + E67A) and C‐lobe (C‐lobe 34 , S101F + E140A) were created by site‐directed mutagenesis using a Quickchange™ kit (QIAGEN) (Fig. 1) [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purification of the GST-fusion proteins was as described in the previous reports [8,12,13] As for CS L fusion protein, the GST portion of it was removed by using the PreScission Protease (GE Healthcare). All steps were performed on ice or at 4°C.…”
Section: Preparation Of Gst-fusion Peptides Of Cav12 and Cs Lmentioning
confidence: 99%
“…The amount of CS L and GST-fusion peptides was corrected based on the relative optical densities of 0.59 and 0.80 in reference to BSA, respectively [8,13]. …”
Section: Gst Pull-down Assay and Data Analysismentioning
confidence: 99%